2006
DOI: 10.1111/j.1745-9125.2006.00049.x
|View full text |Cite
|
Sign up to set email alerts
|

The Multilevel Context of Criminal Sentencing: Integrating Judge- And County-Level Influences*

Abstract: This study extends recent inquiries of contextual effects in sentencing by jointly examining the influence of judge and courtroom social contexts. It combines two recent years of individual sentencing data from the Pennsylvania Commission on Sentencing (PCS) with data on judicial background characteristics and county court social contexts. Three‐level hierarchical models are estimated to investigate the influence of judge and county contexts on individual variations in sentencing. Results indicate that nontriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
414
9
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 284 publications
(445 citation statements)
references
References 44 publications
18
414
9
4
Order By: Relevance
“…They are contrary to the findings of Uhlman (1978), Spohn (1990b), and Steffensmeier and Britt (2001), but conform to the findings of Welch et al (1988), and particularly Johnson (2006) who found that minority judges are less likely to incarcerate black and Hispanic offenders, yet found no difference in the length of sentences. Our findings also coincide with Abrams et al (2008) who found statistically significant between-judge variation (yet not specifically across judge's ethnic identity) in incarceration rates, although not in sentence lengths.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…They are contrary to the findings of Uhlman (1978), Spohn (1990b), and Steffensmeier and Britt (2001), but conform to the findings of Welch et al (1988), and particularly Johnson (2006) who found that minority judges are less likely to incarcerate black and Hispanic offenders, yet found no difference in the length of sentences. Our findings also coincide with Abrams et al (2008) who found statistically significant between-judge variation (yet not specifically across judge's ethnic identity) in incarceration rates, although not in sentence lengths.…”
Section: Discussioncontrasting
confidence: 56%
“…How should we account for the evidence for ethnic in-group bias in the decision to release or detain, and the lack of such bias in the decision on the length of detention, which also mirrors similar findings in the context of sentencing (Johnson 2006, Abrams et al 2008)? The main difference between these two decisions is in the characteristic of the response alternatives -release or detain, as opposed to a range of detention lengths of from one to fifteen days.…”
Section: Judicial Ethnic In-group Bias As Implicit Biasmentioning
confidence: 69%
See 2 more Smart Citations
“…Determinants of post-conviction sentences have long been of interest to criminologists and to researchers from other disciplines who study sanctions (Blumstein et al, 1983;Wooldredge, 2005;Johnson, 2006). Probation decisions have received considerable attention (Morris and Tonry, 1980;Petersilia, 1997).…”
Section: A Split-sample Examplementioning
confidence: 99%